(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Camel milk production and marketing within the peri-urban areas within pastoral areas is emerging and has high potential due to sendentarization and urbanization of an increasing number of local inhabitants. Performance of grazing camels in these areas is poor due to inadequate feed resources, particularly during the dry season. The objective of this study was to determine the effect of supplementing lactating camels with milled Acacia tortilis pods and ‘Chalbi salt’ on milk yield, calf growth and its economic potential in the peri-urban area of Marsabit town, Kenya. Twenty Somali camels in early lactation (1-4 weeks post-partum) and parities 2 or 3 and their calves were recruited for the study. The dams and their calves were penned and fed individually with the supplements where applicable. The treatments were: browsing only (B), browsing and ‘Chalbi salt’ (BC), 2 kg/day milled Acacia tortilis pods, ‘Chalbi salt’ and browsing (BC2A) and 4 kg/day milled Acacia tortilis pods, ‘Chalbi salt’ and browsing (BC4A). Five camels were randomly allocated to each treatment based on initial live weight in a completely randomized design and data collection done for 90 days. During each milking, the two left or right quarters were alternately reserved for the calf, while the remaining two were milked by hand. Milk yields were recorded daily in the morning and evening for 90 days while the calves were weighed on weekly basis for the same period. The overall total mean milk yield during the experimental period ranged from 233.0 to 298.0 litres during the short rains and dry season, respectively. The mean calf weight gains over the study period were 15.2, 19.0, 32.2 and 39.0 kg for B, BC, BC2A and BC4A, respectively, with BC4A and BC2A being higher than B. Supplementing camels under treatment BC4A was profitable as it resulted in both higher milk yield and calf weight gain and hence positive net gain. Int. J. Agril. Res. Innov. Tech. 11(1): 117-122, June 2021